Ricci Tensors with Rotational Symmetry on Rn1 (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
A new, geometric, proof of the existence of smooth solutions of this equation, based on qualitative theory of implicit differential equations, is presented here. This result was obtained previously by DeTurck and Cao in 1994.